Formação de professores e trabalho docente em Cabo Verde - Tavares, Maria dos Reis Moreno (2014)
This thesis aims at discussing the training of teachers and the teaching profession in Cape Verde. The objective of this research is to discuss and question how teacher training has enabled the upgrading of teachers' work and the reinterpretation of the theory-practice relationship in changing formative environments. For operationalization of the proposed research, the methodological approach used here is characterized as qualitative research, highlighting the bibliographical study and document analysis. The construction of the theoretical framework relies on authors like: Feldmann (2009); Garcia (1999); Nóvoa (2006); Tardif and Lessard (2011); Sacristán (1999), among others. The analysis of the collected data allows us to affirm significant advances in different contexts, both in teaching, as well as in the training of teachers, since the country's independence in 1975. However, much more could be done if the country had rethought the diversity of the more complex contemporary academic and professional problem-areas and reflected about the curriculum and study plans, which, to some extent, could offer solutions to the professional challenges in Cape Verde and in the world. The documents indicate that teacher training has not consistently nor appropriately enabled teacher development as desired. Teachers receive in their academic courses, mainly, a theoretical formation and, consequently, present difficulties and limitations in articulating theories as a process of teacher development, that is, to establish in their daily work, the connection between theory and practice. The reasons may be related to the programs and curricula that are not aligned nor adequate to the Cape Verdean reality, especially to the academic and the professional world. Thus, this research finds that there is a need to rethink the policies and guidelines of the government directed to teacher training - initial and continuous - with the aim of coming closer to the desired quality levels in terms of education, teaching, training and research, intensifying, ultimately, the existence of multiple and differentiated contexts of change in Cape Verde and in the contemporary world